Aerosol generation by liquid jet impingement onto a solid surface. (March 2023) - Mbaye, Modou; Sow, Mamadou; Josserand, Christophe
Abstract: Liquid jet impinging onto a surface occurs in many industrial process such as nuclear facilities where a part of radioactive material is handled in liquid form. In the case of accidental leak of this liquid, the airborne particle release, in droplets form, is important to quantify since it is the vector of radioactive air contamination. In the literature, while droplets splashing by drop impact have been extensively studied, only few data are available concerning the airborne particle release fraction and the case of liquid jet impact is even less studied. The purpose of this work is to measure aerosol airborne release when a circular liquid jet impacts a solid surface. We found, when the liquid jet is in the Rayleigh regime, so that the jet is broken into multiple drops before impact, the inertia of the impacting drops influences the amplitude of the aerosols mass size distribution but does not change its shape and consequently the aerodynamic mass median diameter. We also show that particle airborne release depends on the impacting Weber and Ohnesorge numbers through the so-called splashing number K which characterizes the splashing transition. We finally propose a quantitative prediction of the aerosol airborne release fraction, valid for Re ∼   O ( 1 0 3 − 1 0 4 ) and We ∼   O ( 1 0 2 − 1 0 3 ), opening the way to a more general model. Graphical abstract: Highlights: Innovative study on the characterization of aerosolized secondary droplets during a liquid jet impact onto a surface. The mass size distribution, the number of aerosolized secondary droplets have been measured and their generation mechanism has been highlighted. The airborne release fraction of the aerosolized secondary droplets measured has been fitted with the theoretical splashing parameter.